The discarded cow from the flowered desert: revalidation of Gyriosomus crispaticollis Fairmaire, 1886 stat. rev. (Coleoptera: Tenebrionidae) in Southern Atacama, Chile - Guerrero, Marcelo; Diéguez, Víctor M.; Anguita-Salinas, Simón; Reinoso, Álvaro Zúñiga- (Zootaxa, 2023)
Gyriosomus crispaticollis Fairmaire, 1886 is revalidated from the synonymy of Gyriosomus luczotii Guérin-Méneville, 1831 based on the study of G. crispaticollis syntypes and comparative morphological and genetic analyses. Our results suggest that G. crispaticollis is morphologically closer to Gyriosomus multigranulosus Pizarro-Araya & Flores, 2004 than G. luczotii, but genetically barely closer to G. luczotii. Also habitat preferences, field observations and lectotype designation are provided for G. crispaticollis.